2019
DOI: 10.4257/oeco.2019.2302.09
|View full text |Cite
|
Sign up to set email alerts
|

Helminth Community Structure of Two Sigmodontine Rodents in Serra Dos Órgãos National Park, State of Rio De Janeiro, Brazil

Abstract: The fauna and community structure of the helminths of two sympatric sigmodontine rodent hosts, Akodon montensis (Thomas, 1913) and Oligoryzomys nigripes (Olfers, 1818) (Rodentia, Cricetidae) were studied in two areas of an Atlantic Forest reserve, the Serra dos Órgãos National Park in Petrópolis and Teresópolis municipalities, state of Rio de Janeiro, Brazil. During the study, 127 rodents were collected, among which 63 were parasitized (approximately 50%). The helminths recovered from A. montensis were the nem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…The mechanistic approach investigates the contribution of different factors to the metacommunity structure by decomposing the variance of a given set of factors ( Dallas and Presley, 2014 ; Cardoso et al, 2020 ). Host attributes, for example (diet, body mass and abundance) are considered important predictors of host-parasite relationships ( Cardoso et al, 2019 , 2020 , 2021 ; Dallas and Presley, 2014 ; Dallas et al, 2019 ; Kamiya et al, 2014 ). The host's diet can contribute to the acquisition of parasites because many parasites that have indirect life-cycles can be acquired by the consumption of their intermediate hosts ( Leung and Koprivnikar, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanistic approach investigates the contribution of different factors to the metacommunity structure by decomposing the variance of a given set of factors ( Dallas and Presley, 2014 ; Cardoso et al, 2020 ). Host attributes, for example (diet, body mass and abundance) are considered important predictors of host-parasite relationships ( Cardoso et al, 2019 , 2020 , 2021 ; Dallas and Presley, 2014 ; Dallas et al, 2019 ; Kamiya et al, 2014 ). The host's diet can contribute to the acquisition of parasites because many parasites that have indirect life-cycles can be acquired by the consumption of their intermediate hosts ( Leung and Koprivnikar, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nematoda was the most frequent group in this study. Several authors have reported the same findings for other working areas (Cerrado savanna, Pampa grasslands, Caatinga shrubland), and for the same or other small mammal species (Gomes et al, 2003;Navone et al, 2009;Robles, 2011;Simões et al, 2012;Panisse et al, 2017;Hancke & Suárez, 2018;Cardoso et al, 2019). Table 1.…”
Section: Discussionmentioning
confidence: 58%
“…With regard to host age, O. microcephalus showed a higher abundance and prevalence in adult hosts, consistent with the notion of a gradual increase in infection throughout the host lifespan. In contrast, the greater abundance and prevalence of D. logispiculata in young hosts can be attributed to early infections of this helminth, which has previously been observed in helminths in other mammals (Cardoso et al, 2019;Lucio et al, 2021). Larger hosts are expected to have a larger number of parasites and more parasitic species (Guégan et al, 1992;Morand & Poulin, 1998).…”
Section: Discussionmentioning
confidence: 78%